SPIRAPRIL EFFECTS ON OFFICE AND AMBULATORY BLOOD PRESSURE LEVELS AND THEIR DIFFERENCE IN PATIENTS WITH ARTERIAL HYPERTENSION - V. M. Gorbunov; M. I. Smirnova; G. F. Andreeva; A. D. Deev (Российский кардиологический журнал, 2009)
Aim: To investigate the effects of an ACE inhibitor spirapril (S) on office and ambulatory blood pressure (BP) levels, quality of life (QoL) and psychological status (PS) in patients with Stage 1–2 arterial hypertension (AH). Material and methods: This open, randomised cross-over study (4 weeks of spirapril therapy, 4 weeks of amlodipine (A) therapy) included 39 patients with Stage 1–2 AH, aged 53,7±10,0 years; mean AH duration was 11,8±9,5 years. After 7-day wash-out period, S (6 mg) or A (5 mg) were administered; if necessary, A dose was increased to 10 mg; S dose was constant. At baseline and in the end of each treatment phase, 24-hour BP monitoring (BPM), personality traits (Multiphasic Personality Inventory) and QoL (General Well-Being Questionnaire by Marburg University) assessment were performed. No only average levels of office and ambulatory BP, but also the masked hypertension effect (MHE), as an equivalent of masked AH treatment ineffectiveness (MTI), were assessed. MHE was evaluated based on the difference between daytime ambulatory and office BP levels. Results: Both medications were effective in achieving target levels of office and ambulatory AH. MHT value was +1,3±2,0/+0,3±1,3 and +3,6±2,0/+0,3±1,3 mm Hg for S and A treatment, respectively (р<0,05), with initial value of -4,1±1,8/-3,5±1,2 mm Hg. Both medications did not affect QoL and improved some PS parameters. MTI predictors included increased body mass index and electrocardiographic signs of left ventricular hypertrophy (p<0,01– 0,05). MTI risk was lower in older patients, those receiving antihypertensive therapy, consuming moderate doses of alcohol, or having high S7 score (psychasthenia) by MMPI scale (р<0,05). Conclusion: The difference between office and ambulatory BP levels could be explained by various factors. Optimal antihypertensive effect includes achieving target levels for both ambulatory and office BP. Spirapril is an effective antihypertensive medication, facilitating target BP level achievement and PS improvement in AH patients.